Experimental model of autism spectrum disorder induced by prenatal administration of propionic acid to Wistar rats - V. S. Boyarkin; I. G. Kapitsa; T. A. Voronina (LLC "Publisher OKI", 2024)
Relevance. Autism spectrum disorder (ASD) is a developmental disorder of the brain with unclear etiology and pathophysiology, characterized by impaired social communication, stereotypic or repetitive behavior, and varying degrees of mental retardation. One of the environmental factors that have an adverse effect on pregnant women and embryo development is propionic acid (PPA), which is a secondary metabolite of the intestinal microbiota and is widely used as a food preservative. Under physiological conditions, PPC modulates cellular signal transduction, neurotransmitter synthesis and release, cellular interactions, gene expression, immune function, and affects mitochondrial and lipid metabolism. Excessive exposure to PPC can have a number of negative consequences on health and behavior, including leading to the development of ASD.The aim of present research was to assess behavioral characteristics in male and female Wistar rats with ASD caused by prenatal administration of sodium salt of propionic acid at the early perinatal and juvenile stages of development.Methods. In a model of ASD induced by prenatal administration of propionic acid at a dose of 500 mg/kg, subcutaneously on days 12-16 of gestation, behavior was assessed in the "nesting" and juvenile periods of life in male and female Wistar rats. Physical and neurological development, social behavior ("Maternal scent", "Paired test"), repetitive behavior (Y-maze, "Auto-grooming"), motor and exploratory activity ("Mink test") were assessed.Results. In Wistar rats prenatally treated with propionic acid, there was a slowdown in the formation of a number of reflexes at the stage of early postnatal development, and at a later stage - a decrease in social behavior, increased stereotypy and aggression, hyperlocomotion and low exploratory activity.Conclusion. The ASD model induced by prenatal administration of PPC is adequate and suitable for studying means of pharmacological correction of ASD.